Protective Effect of Carvacrol on Oxidative Stress and Cellular DNA Damage Induced by UVB Irradiation in Human Peripheral Lymphocytes. Issue 11 (21st May 2010) - Aristatile, Balakrishnan; Al‐Numair, Khalid S.; Al‐Assaf, Abdullah. H.; Veeramani, Chinnadurai; Pugalendi, Kodukkur Viswanathan
ABSTRACT: Exposure to ultraviolet B (UVB; 280‐320 nm) radiation induces the formation of reactive oxygen species (ROS) in the biological system. In this study, we examined the protective effect of carvacrol on UVB‐induced lipid peroxidation and oxidative DNA damage with reference to alterations in cellular an‐tioxidant status in human lymphocytes. A series of in vitro assays (hydroxyl radical, superoxide, nitric oxide, DPPH (2, 2‐Diphenyl‐1‐picryl hydrazyl), and ABTS (2, 2‐azino‐bis‐3‐ethylbenzothiazoline‐6‐sulfonic acid) radical scavenging assays) demonstrate antioxidant property of carvacrol in our study. UVB exposure significantly increased thiobarbituric acid reactive substances (TBARS), lipid hydroperoxides (LHPs), % tail DNA and tail moment; decreased % cell viability and antioxidant status in UVB‐irradiated lymphocytes. Treatment with carvacrol 30 min prior to UVB‐exposure resulted in a significant decline of TBARS, LHP, % tail DNA, and tail moment and increased % cell viability as carvacrol concentration increased. UVB irradiated lymphocytes with carvacrol alone (at 10 μg/mL) gave no significant change in cell viability, TBARS, LHP, % tail DNA, and tail moment when compared with normal lymphocytes. On the basis of our results, we conclude that carvacrol, a dietary antioxidant, mediates its protective effect through modulation of UVB‐induced ROS.